Superior Mesenteric Artery Aneurysm Presenting with Chronic Abdominal Pain: A Case Report (Cardiovascular Journal, 2016)
Superior mesenteric artery (SMA) aneurysm is a rare vascular entity and may present with a wide range of symptoms. They are often symptomatic, presenting with thromboembolic intestinal angina. They have a high risk of rupture and may present with gastro-intestinal bleeding, associated with high morbidity and mortality. We report the case of a 14year-old boy who presented with chronic abdominal pain and weight loss, in which SMA aneurysm was diagnosed after radiological evaluation. He underwent successful excision of aneurysmal sac along with aorto-mesenteric bypass using polytetrafluoroethylene (PTFE) graft, and had an uneventful recovery.Cardiovasc. j. 2016; 8(2): 161-164